2022
DOI: 10.1073/pnas.2204698119
|View full text |Cite
|
Sign up to set email alerts
|

NETfacts: An integrated intervention at the individual and collective level to treat communities affected by organized violence

Abstract: War and crises affect mental health, social attitudes, and cultural norms, which can exacerbate the state of long-term insecurity. With decades of armed conflict, the Democratic Republic of Congo is one example, and violence has become normalized in civilian settings. In this study, we tested the effectiveness of the NETfacts health system, an integrated model of evidence-based individual trauma treatment (Narrative Exposure Therapy [NET]) and a trauma-informed community-based intervention (NETfacts). Alongsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…All studies found the CBC interventions to Elements of care and intervention approach categories (n = 206). (Green et al, 2020;Robjant et al, 2022) explicitly used the term engagement as an outcome measure. Green et al 's (2020) publication described a telehealth intervention using an artificial intelligence app to provide psychosocial support to pregnant women with depression.…”
Section: Acceptability Feasibility and Engagement In Carementioning
confidence: 99%
See 1 more Smart Citation
“…All studies found the CBC interventions to Elements of care and intervention approach categories (n = 206). (Green et al, 2020;Robjant et al, 2022) explicitly used the term engagement as an outcome measure. Green et al 's (2020) publication described a telehealth intervention using an artificial intelligence app to provide psychosocial support to pregnant women with depression.…”
Section: Acceptability Feasibility and Engagement In Carementioning
confidence: 99%
“…In this publication, engagement was defined as frequency and duration of app usage. On the other hand, Robjant et al 's (2022) publication described a trauma therapy intervention for postconflict communities, where engagement was defined as uptake of trauma-specific treatment after referral. The other five publications examined help-seeking as an outcome (Odenwald et al, 2012;Wright and Chiwandira, 2016;Akena et al, 2021;Atilola et al, 2022;Logie et al, 2022), three of which focused on mental health literacy, the ability to recognize the signs and symptoms of mental illness, understand their causes, and identify sources of help.…”
Section: Acceptability Feasibility and Engagement In Carementioning
confidence: 99%
“…Some transdiagnostic interventions also aim to reduce the risk for other public health issues that commonly affect trauma‐exposed populations in LMICs. For example, NETfacts (Robjant et al., 2022), an adaptation of NET, was found to reduce mental health symptoms, violence perpetration, and stigma towards sexual violence in the DRC. CETA has been found to reduce interpersonal partner violence among Zambian adults living with HIV (Murray et al., 2020), and its effectiveness in improving HIV treatment outcomes is currently being trialed with women experiencing intimate partner violence in South Africa (Pascoe et al., 2022).…”
Section: Flexible Multiproblem Approachesmentioning
confidence: 99%